Profile of male forensic ward patients in the state of Telangana, South India, and the challenges faced - Anitha Rayirala; Umashankar Molanguri; Nagalakshmi Thupkar; Ravikishore Sadula (Telangana Journal of Psychiatry, 2022)
Background: Clinical profiling helps to identify the common psychiatric problems that would result in psychiatric referrals and admissions and helps to develop protocols to counteract common psychiatric problems. Aim: The study aims to identify the profile of forensic ward patients in terms of sociodemographic, clinical, and criminal profiles; evaluate the challenges faced while treating them; and to come up with certain recommendations to the concerned prison authorities to how to deal with them. Materials and Methods: Retrospective chart reviews of 90 male forensic ward inpatients were done and the details as per the semi-structured intake pro forma were taken, and the data were analyzed using descriptive statistical methods. Results: Majority of the patients were single, uneducated, unemployed, and belonged to low socioeconomic status. Referral letters from the concerned prison medical officer were absent in half of the cases. Majority of the patients had personality disorders as the main diagnosis, and antisocial personality disorder was seen in majority (34.4%), followed by substance disorders (32.2%), psychosis (30%), and mood disorders (22.2%). 12.2% of convicted murder individuals diagnosed as schizophrenia. Most common crime committed by the individuals with Anti-social personality disorder was theft (15.6%). Conclusion: In many patients, the information about the reasons for referral and behavioral observation reports was lacking. This lack of information makes it difficult for the psychiatrist to accurately diagnose and treat. Sensitization and creating awareness of prison authorities are of paramount importance to deal with these challenges.